Pengaruh Media Sosial Terhadap Perubahan Perilaku Sosial dalam Masyarakat Modern - Ramadani, Ayu Sinta; Corvina, Nindy Elsa; Mirnawati, Mirnawati; Perawati, Perawati (Indo-MathEdu Intellectuals Journal, 2024)
Social media has become an integral part of everyday life, changing the way individuals interact, communicate, and build social relationships. In the digital era, social media is not only a means of communication, but also a platform for sharing information, expressing one's identity, and building a virtual community. This study discusses the influence of social media on social behavior change in modern society using conceptual methods. This study explores how social media influences social values, interaction patterns, and group dynamics in modern society, both from positive and negative aspects. The data of this study was obtained from literature studies from scientific journals, books, and trusted articles that are relevant to the theme of the influence of social media on social behavior. Through the analysis of social theory and conceptual data, this study provides in-depth insights into the transformation of social behavior due to social media. The results of this study are expected to be a reference in designing a wise social media use strategy to support social cohesion and reduce its negative impact